Evaluation of antioxidant activity of Manihot esculenta Crantz in wistar rats - Satish Eknath Bahekar; Ranjana Sushil Kale (Wolters Kluwer Medknow Publications, 2016)
Aims: The study aimed to explore the antioxidant activity of ethanolic leaf extract of Manihot esculenta Crantz leaves (MEC) in wistar rats. Materials and Methods: Ethanolic extract of MEC leaves in the doses of 50 mg/kg, 100 mg/kg, and 200 mg/kg were used in wistar rats of either sex. The oxidative stress was produced by overdose of acetaminophen and estimation of serum concentration of various enzymes such as malonaldehyde (MDA), superoxide dismutase (SOD), reduced glutathione (GSH), and catalase (CAT) were measured by standard biochemical methods. Silymarin (100 mg/kg) was used as a standard drug for assessment of antioxidant status. Statistical Analysis Used: Results were analyzed by one-way analysis of variance followed by Student's unpaired t-test. Results: When compared with the standard antioxidant silymarin, MEC extract did not exhibit antioxidant activity in terms of MDA level reduction. However, it significantly increased serum levels of the antioxidant enzymes (SOD, GSH, and CAT) exerting a potent antioxidant effect in a graded manner. Conclusions: The observed results suggest that MEC could be a potential source of antioxidants. However, further studies are required to explore this therapeutic property of plant.